The Perceptions of digital technology at a New Zealand tertiary institution - Singh, Umang (Pacific Journal of Technology Enhanced Learning, 2022)
The way educational institutions view certain technology has changed dramatically over the years, especially with the world lockdown in 2020. Understanding how digital technology is seen in an educational institution is the path to finding out how to improve and enhance the learning experience for students. A study by the OECD (Organisation for Economic Co-operation and Development) showed “digitalisation has been one of the main drivers of innovation in educational practices in the classroom in the past decade.” (Vlies, 2020)